A conceptual framework in determining psychological well-being among school middle leaders - Md. Hanafiah, Jama’yah; Mohd. Rasdi, Roziah; Musa, Siti Nur Syuhada (Springer Nature, 2024)
This paper is proposing a conceptual model of psychological well-being among Malaysian school middle leaders who works in primary school. Psychology of Working Theory and Self-Determination Theory both are used as the underpinning theory in this conceptual framework. A thorough study of the literature was conducted to find and interpret relevant studies, to develop a psychological well-being model. The two potential predictors on psychological well-being of school middle leaders are decent work and self-determination needs. The paper proposes competence, autonomy, and relatedness as dimension in self-determination needs as the mediators between decent work and psychological well-being. Based on a systematic review, this paper uses the exploratory investigation. Perception of SML on their working condition affects the psychological health of middle school leaders. The application of decent work scale is ultimate features that extricate this study among school middle leaders in Malaysia. This could provide new insights to promote psychological well-being in school subject to model validation. Therefore, it is anticipated that this study will contribute to the theoretical development of linking decent work to psychological well-being via the mediating effects of competence, autonomy, and relatedness, that will benefits academics and practitioners.